2018
DOI: 10.1016/j.mayocpiqo.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

At the Intersection of Patient Experience Data, Outcomes Research, and Practice: Analysis of HCAHPS Scores in Neurology Patients

Abstract: ObjectiveTo assess variation in patient-reported experience in inpatient neurology patients.Patients and MethodsWe retrospectively identified 1045 patients 18 years and older admitted to a neurology service and discharged from January 1, 2013, through September 30, 2016, who completed Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) surveys. Multivariable logistic regression evaluated the associations of patient factors with HCAHPS measures. Key driver analysis identified associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…13 A mere glance at Figure 1 reveals the unique position of care transition among all SQ attributes. Based on that analysis, the SQ variable nurse communication achieves the closest position (nurse communication = 75.31; r = 0.822) to overall rating, as was previously described, 22,23 while the newly published HCAHPS measure care transition is solely positioned in quadrant IV (care transition = 46.27; r = 0.804). Thus, for providers and health care policy makers, care transition has the most potential for improvement, as compared to the other SQ attributes.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…13 A mere glance at Figure 1 reveals the unique position of care transition among all SQ attributes. Based on that analysis, the SQ variable nurse communication achieves the closest position (nurse communication = 75.31; r = 0.822) to overall rating, as was previously described, 22,23 while the newly published HCAHPS measure care transition is solely positioned in quadrant IV (care transition = 46.27; r = 0.804). Thus, for providers and health care policy makers, care transition has the most potential for improvement, as compared to the other SQ attributes.…”
Section: Discussionmentioning
confidence: 60%
“…where OR represents the dependent variable overall rating, X 1 is the care transition scores, and X 2 is the interaction variable, having a value of 0 or 1. Finally, a key driver analysis 22 was conducted to identify composite attributes that are important drivers of overall rating. Such attributes are classified by a low SQ score on the one hand and being highly correlated with the overall rating score on the other.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 10 812 studies identified, 18 were included, describing 13 PREMs [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] (Figure ; Table II in the Data Supplement). Two PREMs, Consumer Quality Index: Cerebrovascular Accident (CQI-CVA) 16 and Riksstroke, 13 had been developed for stroke care.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the risk of acquiescence bias (the tendency for survey respondents to select positive response options) [13], we focused our reporting of agreement on the percentage of respondents who selected "strongly agree", thus actively indicating a strong preference in favor of each recommendation. As clinicians' level of support for a clinical practice guideline has been associated with their adherence to guidelines in practice [14,15], this type of top-box analysis-used often in patient experience surveys [16][17][18]-may best predict clinicians' real-world behavior. We calculated 95% confidence intervals for the percentages of respondents who strongly agreed with each recommendation; average margin of error across all recommendation was 12.7% (Supplementary Information).…”
Section: Discussionmentioning
confidence: 99%